2019
DOI: 10.1080/19420889.2019.1643665
|View full text |Cite
|
Sign up to set email alerts
|

CYRI/ Fam49 Proteins Represent a New Class of Rac1 Interactors

Abstract: Fam49 proteins, now referred to as CYRI (CYFIP-related Rac Interactor), are evolutionarily conserved across many phyla. Their closest relative by amino acid sequence is CYFIP, as both proteins contain a domain of unknown function DUF1394. We recently showed that CYRI and the DUF1394 can mediate binding to Rac1 and evidence is building to suggest that CYRI plays important roles in cell migration, chemotaxis and pathogen entry into cells. Here we discuss how CYRI proteins fit into the current framework of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In summary, we have revealed the structure of CYRI-B, also called FAM49B, the only described negative regulator of cellular actin assembly mediated by the WAVE regulatory complex (WRC;Fort et al, 2018;Whitelaw et al, 2019). Our structure, the first to be reported of any member of the CYRI family, reveals a protein that is entirely composed of -helices and organized into three distinct subdomains.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…In summary, we have revealed the structure of CYRI-B, also called FAM49B, the only described negative regulator of cellular actin assembly mediated by the WAVE regulatory complex (WRC;Fort et al, 2018;Whitelaw et al, 2019). Our structure, the first to be reported of any member of the CYRI family, reveals a protein that is entirely composed of -helices and organized into three distinct subdomains.…”
Section: Resultsmentioning
confidence: 70%
“…FAM49B was consequently renamed CYRI-B for CYFIP-related Rac1 interactor (Fort et al, 2018). CYRI-B binding has been reported to block various Rac1-dependent signalling cascades in the cell, thereby controlling multiple critical cellular functions including T-cell activation (Shang et al, 2018), membrane protrusion, chemotaxis and cell migration (Fort et al, 2018;Whitelaw et al, 2019). By negatively regulating Rac1 signalling, CYRI-B also reduces the entry of several intracellular bacterial pathogens into both phagocytic and non-phagocytic host cells, and indeed is targeted for ubiquitin-mediated destruction by the action of an injected Salmonella virulence protein (Yuki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rac1 P29S is a clinically important mutation ( Hodis et al., 2012 ; Krauthammer et al., 2012 ), as it allows Rac1 to undergo spontaneous nucleotide exchange in the absence of a GEF, producing a shift to active Rac1 ( Davis et al., 2012 ). It has been reported that the dual mutation P29S Q61L increases the affinity of Rac1 to CYRI-B and not other effectors such as the CRIB domain ( Fort et al., 2018 ; Whitelaw et al., 2019 ). As P29 is located at the binding interface between Rac1 and CYRI-B ( Figure 3 A), one could speculate that mutation to a serine could result in additional hydrogen bonds, perhaps with R161 to increase the affinity of the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The FAM49A gene, also known as CYRI-A, encodes CYFIP-related Rac1 interactor A, a highly conserved regulator of the small GTPase RAC1, to which it binds [38]. FAM49A is expressed in the brain where the protein regulates chemotaxis, cell migration and epithelial polarization [39].…”
Section: Two Genes Upregulated By All Four Drug Treatments In U87mgmentioning
confidence: 99%